Early Shared Reading Is Associated with Less Harsh Parenting. Issue 7 (September 2019) - Jimenez, Manuel E.; Mendelsohn, Alan L.; Lin, Yong; Shelton, Patricia; Reichman, Nancy
ABSTRACT: Objective: Shared reading is believed to enhance parent-child relationships, but the extent to which it reduces harsh parenting is understudied. Associations between early shared reading and subsequent harsh parenting were investigated. Methods: Data from a national urban birth cohort were used to estimate associations between mother-reported shared reading at ages 1 and 3 years and harsh parenting—based on a composite of psychological and physical aggression subscales of a validated self-report instrument—when the children were at ages 3 and 5 years. The authors used multivariable linear regression and generalized estimating equations to account for repeated observations. Given potential inverse associations between shared reading and child disruptive behaviors, which can trigger harsh parenting, the authors investigated the extent to which children's behavior at age 3 years mediated the association between shared reading at age 1 year and harsh parenting at age 5 years. Results: This study included 2165 mother-child dyads. Thirty-four percent and 52% of mothers reported daily reading at ages 1 and 3 years. In adjusted models, shared reading at age 1 year was associated with less harsh parenting at age 3 years. Similarly, shared reading at age 3 years was associated with less harsh parenting at age 5 years. These associations remained significant in lagged repeated-measures models. Decreased disruptive behaviors partially mediated the association between shared reading at age 1 year and harsh parenting at age 5 years. Conclusion: Shared reading predicted less harsh parenting in a national urban sample. These findings suggest that shared reading contributes to an important aspect of the parent-child relationship and that some of the association operates through enhanced child behaviors.